Upaya meningkatkan proses pembelajaran melalui lesson study pada pendidik PAUD se-Korwil Dindikpora Kecamatan Kranggan Kabupaten Temanggung - Lilik Hidayati (Universitas Sebelas Maret, 2020)
The classic problem in the learning process conducted by the teacher is that the teacher is still the center of attention; the teacher does not use learning media; The teacher does not innovate in learning. These classic problems must be immediately addressed so that the learning process becomes more interesting. One way to fix the problem is the teacher participates in lesson study activities. In this study, researchers wanted to find out how effective lesson study was able to improve teacher competence in the learning process in PAUD. This school action research takes place in PAUD throughout the Dindikpora Regional District Kranggan District Temanggung Regency T.A. 2019/2020, with a total of 12 research subjects. Implementation of activities carried out through 2 cycles. The data analysis technique uses qualitative analysis which is used for qualitative data obtained from teacher observations during the learning process and during the lesson study. The results of this action research are: 1) Lesson study improves the ability of teachers in the learning process in PAUD throughout Dindikpora Regional District Kranggan District Temanggung Regency 2019/2020 Academic Year by 12.35%, in the good category.